PEMANFAATAN SAMPAH DAPUR SEBAGAI PUPUK ORGANIK CAIR UNTUK TANAMAN PEKARANGAN DAN HORTIKULTURA DI DESA ILOTIDEA KECAMATAN TILANGO KABUPATEN GORONTALO (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
The purpose of KKN-T community service activity is to increase the creativity of students and the community of Ilotidea Village in utilizing kitchen waste as the Liquid Organic Fertilizer (LOF) which can increase plant growth in the yardland. In Ilotidea Village, the community is very enthusiastic about utilizing yardland, unfortunately, has not managed kitchen waste as fertilizer that can add nutrients to the growth and production of plants. Benefits: 1) management of kitchen waste as an organic fertilizer manufacturing material, 2) produce LOF for cultivation crop in the yardland. Methods in the form of socialization, training, and applications of making organic fertilizers, vegetable cultivation, and simple planting pattern techniques in the yard. This activity was attended by 14 students of the Department of Agrotechnology and the village community. The results of activities: socialization of the use of kitchen waste as LOF, land use of yards, the exhibition of LOF product products in the village. Additional activities include the management of flood disasters, sports and arts development and the vaccination movement. External in the form of the publication of videos and articles.